Cost analysis of four types of surgeries for pelvic organ prolapse in a Japanese population. Issue 4 (25th January 2021) - Myoga, Mai; Sho, Tomoko; Aoki, Hitomi; Ishizuka, Takaki; Nakajima, Daisuke; Yoshimura, Kazuaki
Abstract: Introduction and Hypothesis: To compare the perioperative costs analysis between laparoscopic/transvaginal and the mesh/non–mesh surgeries for pelvic organ prolapse (POP) in Japan. Materials and Methods: From April 2013 to April 2017, 890 patients who underwent POP surgeries were enrolled in this study. Regarding transvaginal native tissue repair (TV‐NTR: transvaginal hysterectomy with colpocleisis), transvaginal mesh surgery (TVM), laparoscopic native tissue repair (L‐NTR: laparoscopic hysterectomy and uterosacral ligament colposuspension), and laparoscopic sacrocolpopexy (LSC), a retrospective observational study was performed. Patients' age, operation time, blood loss, perioperative complications, length of hospital stay, pre‐/postoperative quality of life (QOL) scores, were reviewed from the medical records. The net income, which was calculated by using the income (the operation/anesthesia fee) and the costs (the labor and consumables costs for operation/anesthesia), was evaluated. Results: The operation fees of the L‐NTR ($4250) and the LSC ($4833) groups were higher than that of the TV‐NTR ($2652) and the TVM ($2913) groups. The labor costs and consumables costs of operation were higher in the LSC ($1589) and the L‐NTR ($1500) groups than the TV‐NTR ($180) and the TVM ($178) groups. The consumables costs for anesthesia in the four groups were equal. The operation hours were significantly shorter in the TV‐NTR and the TVM groups than the L‐NTR and the LSC groups. Conclusions: We found that TVM operation was an economically excellent and the most efficient POP operation with shorter operation time and less consumables.